Effectiveness of Systemic Inflammation Response Index (SIRI) Neutrophil–Lymphocyte Ratio (NLR), Derived Neutrophil–Lymphocyte Ratio (dNLR), and Systemic Immune Inflammation Index (SII) for predicting prognosis of acute diverticulitis - Yıldız, Yasin Alper (Springer Science and Business Media LLC, 2025)
Abstract There are many applications to emergency services due to acute colonic diverticulitis. It is necessary to decide whether these patients are complicated, to quickly predict their prognosis, and to decide whether medical or invasive treatment is necessary. We planned to research effectiveness NLR, NLR, SII, and SIRI values calculated using hemogram data can predict the prognosis of acute diverticulitis. We managed a retrospective scanning with patients who applied with a diagnosis of acute diverticulitis between 06/2020 and 04/2023. Demographic data (age, gender, previous surgery, comorbid diseases), tomographic Hinchey classification, location of diverticulitis, applied treatment, and obtained from blood parameters at presentation to the emergency department WBC, CRP, NLR, dNLR, SII, SIRI parameters were recorded from the electronically registered patient files. According to the Hinchey classification, those with Hinchey 0 and 1a were included in the noncomplicated group A class because they were followed up with outpatient medical follow-up. Those with Hinchey 1b,2,3,4 were included in the complicated GROUP B class. Differences in WBC, CRP, NLR, dNLR, SIRI, SII values between the complicated and noncomplicated groups were evaluated statistically. There were 286 patients with acute diverticulitis on the dates indicated. The number of patients eligible for the study was eighty-two. According to Hinchey’s classification, 56 patients had noncomplicated acute diverticulitis (SAD) and 26 patients had complicated diverticulitis (CAD). These diagnoses were given based on tomography findings and clinical evaluations. The hospital stay was longer in the CAD group compared to the SAD group (p < 0.001) statistically significantly. The rate of surgical procedures and percutaneous interventions in the CADs was higher than SADs (p: 0.040) statistically significantly. WBC (white blood cell), NLR, dNLR, SIRI, SII and CRP parameters were higher in CADs than in SADs as statistically significant. Spearman’s correlation analysis showed between the Hinchey classification and the NLR, dNLR, SII, SIRI, CRP, WBC parameters with high correlation as positive. Determination of values SIRI (2.42), NLR (3.35), SII (907.44) dNLR (4.63), CRP (15.25) WBC (11.16) and specificity and fractionation of these values ROC analysis was performed for this purpose. Highest AUC (area under the curve) value was found in WBC [0.807 0.703–0.910)], SIRI [0.786 (, 0.681–0.892)], SII [0.767 (0.654–0.880)], NLR [0.740 (0.624–0.854)], dNLR [0.739 (0.625–0.853)]. This study showed that there are SII, SIRI dNLR, NLR, CRP, and WBC values in patients presenting with acute diverticulitis a very high correlation with Hinchey classification in distinguishing complicated and non-complicated acute diverticulitis (p < 0.01). These data were higher in CADs than in SADs statistically significantly. The use of these data can both prevent unnecessary radiation in patients suspected of acute diverticulitis by reducing unnecessary tomography scans and can be valuable in predicting the prognosis of diverticulitis at a low cost.